Countering vulnerability and enhancing resilience: coastal agriculture in West Bengal, India - S M Rahaman; B K Bera; Subhadip Pal; A K Nandi; Surajit Haldar (Agricultural Economics Research Review, 2023)
We analyse the economics of 14 farming systems in the Sundarban region of West Bengal, India. Most of the farmers in our sample (84.53%) were smallholders who practised a cereals-based farming system limited to monocropping kharif paddy (18.89%). We suggest two farm plans that require farmers to reallocate their resources to vegetable farming, fishery, poultry farming, and rearing dairy animals. One plan, at the existing level of resources, can increase net income by more than 25% over the existing plan. The other plan, at an enhanced level of resources, could increase net income by more than 45%.